Application of Relational Mindfulness in Management Education : Development and Validation of Relational Mindfulness Training (RMT) - Vich, Marek; Lukeš, Martin, 1976-; Pauknerová, Daniela, 1970-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2017)
The application of mindfulness in management practice and education has recognized notable growth in recent years. The development of mindfulness has shown positive effects in several domains such as stress management, work engagement, well-being and cognitive flexibility. However, the effect of mindfulness training in the domain of interpersonal relationships is still a rather unexplored area. Furthermore, little evidence has so far explored the domain of relational mindfulness that focuses on the development of awareness of one and other’s condition in a social context. In order to address the lack of evidence, the goal of this thesis is to develop and validate an 8-week mindfulness-based intervention (MBI) named Relational Mindfulness Training (RMT). Research was conducted in the pilot (N = 66) and main study (N = 128) that included students of the University of Economics in Prague. Results showed a significant effect of participation in RMT on mindfulness, self-compassion, authentic leadership, compassion, perceived stress and subjective happiness. Results from the main study further confirmed significant effects of RMT participation on mindfulness, self-compassion and perceived stress in the long run, and indicated that individuals who maintained the individual practice after the end of intervention showed notably better results than individuals who did not. However, the individual practice did not affect the level of compassion. It suggests that an increase of compassion was not affected by an individual practice but by a relational practice of RMT. Two studies described in this thesis are the first ones that validate the effects of a relational-based mindfulness program in management education and the first ones to validate the effects of MBI in the Czech Republic.
They also suggest that training in relational mindfulness has a potential to become a beneficial part of management education curriculum as it may help future leaders to handle their challenges in more aware and caring way.
Vedoucí práce: Martin Lukeš
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: podniková ekonomika a management [obor disert. práce]; disertace; dissertations